SUBJECT AND CONSUMPTION ... AN EDUCATIONAL CHALLENGE - Ospina Nieto, Yovany (Universidad Pontificia Bolivariana, 2020)
The current world is constantly energized by market demands, which in one way or another permeate the construction of subjectivities, people are conditioned by the consumer society and the offers that it puts before it. In this context, new social and cultural forms of relationship emerge, which end up deconstructing the existential condition of the human being. In this existential deconstruction, the human being identifies with the demands of the market and feels attracted to a consumer society that even conditions its formation, since the educational system is not alien to this reality. This is how a subject objectified by market demands underlies. The foregoing warns of a dehumanizing process of the person, which ends up focusing all its capacities on mere production. In this regard, Corrales (2005) says: In this approach, consumption appears guided by “objective” needs and goods are consumed according to the importance of said needs and the amount of resources available to satisfy them: consumers are seen as subjects individual, free and rational, who make their consumption decisions according to an exact calculation guided by an evaluation of the cost-benefit type, is the realm of the Weberian homo economicus. (p. 211)